Unlocking blue foods resources for food and nutrition security in Indonesia - Sarah Firdausi; Ibnu Budiman (Center for Indonesian Policy Studies (CIPS), 2025)
Increasing blue foods production and consumption to reach its potential is critical for achieving food security and the eco-regionalization of the food system. Increasing blue food consumption requires a market approach with a focus on the availability, accessibility, market growth phases, and cultural preferences of consumers. The Ministry of Marine Affairs and Fisheries and Bappenas must include data of blue foods such as consumer preferences, regional distribution, import and export value by type of fish, and consumption by type of fish at the sub-national level and Blue Food Assessment results to the Indonesia Food System Dashboard (DSPI) to allow for evidence-based policy planning.
Keywords: 330